ANALISIS ASPEK FONETIK DAN FONEMIK BAHASA DAYAK DUSUN TUMBANG DESA MAGALAU HULU KECAMATAN KELUMPANG BARAT KABUPATEN KOTABARU - Husni Mubarak (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2014)
ABSTRACT                Phonetic aspect is a branch of linguistics that studies the sounds of language. Thus, in a study entitled "Analysis of Phonetic and phonemic language Dayak village tumbles Village Magalau Hulu subdistrict Kelumpang West Kotabaru District." The researchers managed to find aspects of phonetic form of language sounds contained in colloquial language Dayak village tumbles as the sound of the vocal cords slightly open, wide open, mengencup, and the sounds of the language that is issued through the upper and lower lip and lower lip with a combination of upper teeth called phonemic labiodentals.Aspek is a branch of linguistics that is the same as the phonetics, but the difference is more specifically phonemic learn the meaning of the language difference dikeluarakan by the human vocal organs. In the study of language dayak tumbles, researchers managed to find distinguishing the meaning of each conversation as a differentiator between the consonants / r / of the word ma market and / r / from said marauh, so that from these two words there is a difference of meaning which is called phonemic aspects. Keywords :  Aspect  fonetik ,  Aspect fonemik